Are Data from Mycotoxins' Urinary Biomarkers and Food Surveys Linked? A Review Underneath Risk Assessment. Issue 4 (19th May 2021) - Martins, C.; Assunção, R.; Nunes, C.; Torres, D.; Alvito, P.
ABSTRACT: Mycotoxins are natural chemical contaminants of foods, posing several health risks to humans. Biomarkers-driven research has been used as a tool for a more accurate characterization of the internal exposure. Whether certain food items are predictors of exposure to mycotoxins constitutes an important aspect for the risk assessment of mycotoxins. Comprehensive human biomonitoring studies linked with food surveys and health studies are of utmost importance, contributing to identify the determinants of exposure. Associations between mycotoxins' urinary biomarkers and consumption of some food items were reported. This review is focused on the link between mycotoxins' urinary biomarkers and food consumption.